2011
DOI: 10.1007/s11434-011-4838-8
|View full text |Cite
|
Sign up to set email alerts
|

Trend in the atmospheric heat source over the central and eastern Tibetan Plateau during recent decades: Comparison of observations and reanalysis data

Abstract: The trend in the atmospheric heat source over the central and eastern Tibetan Plateau (CE-TP) is quantitatively estimated using historical observations at 71 meteorological stations, three reanalysis datasets from 1980-2008, and two satellite radiation datasets from . Results show that a weakening of sensible heat (SH) flux over the CE-TP continues. The most significant trend occurs in spring, induced mainly by decelerated surface wind speeds. The ground-air temperature difference shows a notable increasing tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 25 publications
5
27
0
Order By: Relevance
“…Such changes have invited crucial questions, such as how atmospheric variations and surface changes impact the SRB over the TP, how the decadal dimming and brightening affect the environment and climate [ Wild , ], how the SRB over the TP responds to rapid warming [ Qin et al ., ], and how the SRB and latent and sensible heat fluxes over the TP are related to the East Asian monsoon climate [ Duan et al ., ; Wu et al ., ]. However, few studies have attempted spatiotemporal characterization of the SRB components over the entire TP in recent decades, for several reasons: limited sites for ground measurement [ Stone , ; Bookhagen , ], poor accuracy of remote sensing products [ Pinker et al ., ], and inconsistent trends derived from multiple reanalysis products [ Tang et al ., ; Wang et al ., ]. Part 1 of this two‐paper series described an effective data fusion method that synthesized ground observations, reanalysis products, and remote sensing data sets at 0.5° spatial resolution from July 1983 to December 2007 with RMSEs <20 Wm −2 for radiation fluxes and 0.05 for albedo.…”
Section: Introductionmentioning
confidence: 99%
“…Such changes have invited crucial questions, such as how atmospheric variations and surface changes impact the SRB over the TP, how the decadal dimming and brightening affect the environment and climate [ Wild , ], how the SRB over the TP responds to rapid warming [ Qin et al ., ], and how the SRB and latent and sensible heat fluxes over the TP are related to the East Asian monsoon climate [ Duan et al ., ; Wu et al ., ]. However, few studies have attempted spatiotemporal characterization of the SRB components over the entire TP in recent decades, for several reasons: limited sites for ground measurement [ Stone , ; Bookhagen , ], poor accuracy of remote sensing products [ Pinker et al ., ], and inconsistent trends derived from multiple reanalysis products [ Tang et al ., ; Wang et al ., ]. Part 1 of this two‐paper series described an effective data fusion method that synthesized ground observations, reanalysis products, and remote sensing data sets at 0.5° spatial resolution from July 1983 to December 2007 with RMSEs <20 Wm −2 for radiation fluxes and 0.05 for albedo.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing greenhouse gas can significantly influence the global and regional dust cycle through affecting the climate, veg- 25 etation and dust-climate feedbacks although there exists large uncertainty in the response of the global dust loading to future climate change (Harrison et al, 2001;Tegen et al, 2004;Mahowald et al, 2006;Kok et al, 2018). Additionally, the surface sensible flux over TP exhibits a remarkable weakening trend under global warming, induced primarily by weakened surface wind speeds (Duan et al, 2011;Wang et al, 2012;Yang et al, 2014). Our study shows the importance of the TPSH on the change in East Asian dust cycle through affecting the westerly winds.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies (Monin and Obukhov 1954, Duan and Wu 2008, Wang et al 2012, Duan et al 2018b, SH can be calculated by the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the SH over the TP has been proved to be undergoing a decreasing trend, especially in spring season (Duan and Wu 2008, Wang et al 2012, Wang and Ma 2018. Duan and Wu (2008) suggested that this weakening trend in SH was induced mainly by the steadily decreased surface wind speed, which was linked to climate warming (Duan and Wu 2009).…”
Section: Introductionmentioning
confidence: 99%